Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai di Rumah Sakit Umum Daerah Mamuju - Wanda Wanda; Chalid Imran Musa; Ikhwan Maulana Haeruddin; Agung Widhi Kurniawan; Rezky Amalia Hamka (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to determine the influence of workload and work environment on employee performance at the Mamuju Regional General Hospital. The type of research used is quantitative. The sample in this study was 40 nurses as respondents. Data analysis used multiple linear regression equations and hypothesis verification using the t test, F test and coefficient of determination (R²) using the Statistical Package for Social Science (SPSS). The results of this research are that workload (X1) has a negative effect on employee performance at the Mamuju Regional General Hospital. Work Environment (X2) has a positive and significant effect on employee performance at the Mamuju Regional General Hospital. Workload (X1) and work environment (X2) significantly influence the performance of Mamuju regional public hospital employees.